Silence in Arabic Cross-Cultural Interaction - Atyaf Hasan Ibrahim; Ramadhan M. Sadkhan; Adil Malik Khanfar (JELITA, 2021)
This study investigates silence as a nonverbal manner of communication cross-culturally in Arabic to expose if it is as powerful as the verbal communication. It concentrates on the distinct types, forms and functions of silence in different contexts and the way it is perceived by the communicators. The study concluded that silence has a great value cross-culturally in Arabic, and is as effective as speech in transmitting messages and serving the goal of the interaction. Speech and silence are closely related and exist almost in every interaction. Each way has an important function and that they come to have greater effect when used together. Silence has many exceptional functions aside from accepting a matter or refusing it such as preserving other’s dignity and making them avoid behaving impolitely. Silence acts as a face-saving such as dumb founded and as a face-threatening technique such as cunning.